1999
DOI: 10.1002/hep.510290519
|View full text |Cite
|
Sign up to set email alerts
|

Lipoic Acid Prevents Development of the Hyperdynamic Circulation in Anesthetized Rats With Biliary Cirrhosis

Abstract: Chronic bile duct ligation is associated with the development of oxidant injury, biliary cirrhosis, portal hypertension, and a hyperdynamic circulation. We have previously demonstrated that the hyperdynamic circulation in the partial portal vein-ligated rat can be prevented by the administration of N-acetylcysteine. To extend these findings, we have examined the effect of lipoic acid, a thiolcontaining antioxidant, on hemodynamics, oxidative stress, and nitric oxide (NO) production in bile duct-ligated (BDL) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
43
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 39 publications
6
43
0
Order By: Relevance
“…BDL is associated with the development of oxidant injury, hepatic fibrosis, biliary cirrhosis, portal hypertension, and a hyperdynamic circulation that is a dynamic process implying different rates of progres- sion or regression (18). It has been reported that BDL reduces antioxidant defences and increases free radical formation (19).…”
Section: Discussionmentioning
confidence: 99%
“…BDL is associated with the development of oxidant injury, hepatic fibrosis, biliary cirrhosis, portal hypertension, and a hyperdynamic circulation that is a dynamic process implying different rates of progres- sion or regression (18). It has been reported that BDL reduces antioxidant defences and increases free radical formation (19).…”
Section: Discussionmentioning
confidence: 99%
“…31 There is now good evidence that liver disease is associated with oxidative stress and increased formation of reactive oxygen species. 32,33 Ljubuncic et al reported an increased formation of lipid peroxidation products in the cardiac tissue of rats with biliary cirrhosis compared with controls. 33 This finding may be partly owing to enhanced generation of superoxide by NADPH oxidase in response to angiotensin II, 34 endothelin, 35 bile acids, 36 or can occur secondary to the formation of peroxynitrite.…”
Section: Discussionmentioning
confidence: 99%
“…37 We have previously observed that administration of N-acetylcysteine normalizes the systemic hemodynamic abnormalities in rats with portal hypertension, 16 and lipoic acid (another low molecular weight thiol antioxidant) had a similar effect in rats with chronic bile duct ligation. 32 Therefore, we investigated whether N-acetylcysteine could improve cardiac function in rats with biliary cirrhosis, and made the critical observation that administration of N-acetylcysteine led to normalization of bradycardia in vivo, as well as improved cardiac responses to adrenergic stimulation in vitro (Figs. 1 and 2).…”
Section: Discussionmentioning
confidence: 99%
“…The oxidative stress known to occur as a systemic response to cholestasis could give rise to the involvement of organs other than liver, such as the kidney, which could explain the renal morphological and functional alterations here reported 19 . This contention is based on previous studies 21 , which found that the antioxidants -lipoic acid and N-acetylcysteine prevented the hyperdynamic circulation induced by either experimental cholestasis or portal hypertension. Another study further supported this notion, as vitamin E prevented the fall in blood pressure and restored PRA to normal (likely because of the improved hemodynamic state) 22 .…”
Section: Renal Morphologymentioning
confidence: 97%